LA CITTÀ PALINSESTO/II Tracce, sguardi e narrazioni sulla complessità dei contesti urbani storici: Rappresentazione, conoscenza, conservazione - Pascariello, Maria Ines (Storia e iconografia dell'architettura, delle città e dei siti europei, 2020)
This volume contains the most recent reflections on the necessary foundations, theoretical and thought, as well as the technical, artistic, technological aspects that lead to conceiving the city and the landscape as a figurative and phenomenological palimpsest. City and landscape, in fact, continually subject to erasing and rewriting operations - in terms of project and restoration, protection and enhancement, design and redesign - are the visual witnesses of how the schedule appears to us today, thanks to the increasingly squeezed between technologies and tools of vision, in a highly relational projective and transformative perspective.